1995
DOI: 10.1128/aac.39.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity and structure-selectivity studies on diaminoquinazolines and other inhibitors of Pneumocystis carinii and Toxoplasma gondii dihydrofolate reductase

Abstract: Twenty-eight 2,4-diaminoquinazolines with alkyl, halogen, or alkoxy groups at the 5-, 6-, and/or 7-position, eight 2,4-diaminopteridines with alkyl and aralkyl groups at the 6-and 7-positions, five 1,3-diamino-7,8,9,10-tetrahydropyrimido[4,5-c]isoquinolines with an alkyl, alkylthio, or aryl group at the 6-position, and nine 4,6-diamino-1,2-dihydro-s-triazines with one or two alkyl groups at the 2-position and a substituted phenyl or naphthyl group at the 1-position were evaluated as inhibitors of dihydrofolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
(54 reference statements)
2
20
0
Order By: Relevance
“…These lipophilic DHFR inhibitors are assumed to cross the plasma membrane by passive or facilitated diffusion and, therefore, to obviate drug susceptibility and resistance problems associated with carrier-or receptor-mediated folate transport mechanisms (7). Many of these compounds have previously been assayed against P. carinii DHFR and T. gondii DHFR-TS in vitro (48,49,(51)(52)(53)(54)(55)(56). For example, the IC 50 of PY875 against the P. carinii DHFR enzyme in vitro was ϳ7 M (51), suggesting that PY875 might also inhibit the growth of Pc-yeast; Table 6 shows this to indeed be the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These lipophilic DHFR inhibitors are assumed to cross the plasma membrane by passive or facilitated diffusion and, therefore, to obviate drug susceptibility and resistance problems associated with carrier-or receptor-mediated folate transport mechanisms (7). Many of these compounds have previously been assayed against P. carinii DHFR and T. gondii DHFR-TS in vitro (48,49,(51)(52)(53)(54)(55)(56). For example, the IC 50 of PY875 against the P. carinii DHFR enzyme in vitro was ϳ7 M (51), suggesting that PY875 might also inhibit the growth of Pc-yeast; Table 6 shows this to indeed be the case.…”
Section: Resultsmentioning
confidence: 99%
“…The activities of many of these drugs against these parasites or their purified DHFR enzymes was known already. For example, members of the PY series had been tested in vitro to measure inhibition of the P. carinii or T. gondii enzyme (48,49,(52)(53)(54)56). We knew at the outset which compounds were effective in vitro against the DHFRs of other pathogens, which allowed us to quickly identify drugs that did not effectively penetrate the yeast host.…”
Section: Discussionmentioning
confidence: 99%
“…Representative compounds from each data set are shown in Figure 2 . The experimental IC 50 values for the dihydrofolate reductase (DHFR) inhibitor set were calculated and reported [ 16 , 19 , 22 , 26 ] for the DHFR enzyme from three different species: P. carinii (PC), T. gondii (TG) and rat liver (RL), where the activity of the DHFR inhibitors to the enzymes from different species differ. Therefore, activities of the inhibitors towards the enzymes from these three species for DHFR inhibitors are studied separately in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Studies published to date, which have evaluated a total of around 200 entities against P. carinii DHFR and T. gondii DHFR, suggest that while the relationship between structure and activity against the two enzymes is distinct, there is a possibility that the identification of entities with potent activity against both enzymes is achievable (7,14,15). A series of 15 6-substituted 2,4-diaminopyrimidines, which are closely related to the structures described in this study, have been shown to contain nanomolar inhibitors of both P. carinii DHFR and T. gondii DHFR (7).…”
Section: Discussionmentioning
confidence: 99%